Low-Temperature Ionothermal Synthesis of Li-Ion Conductive Li4B7O12Cl Solid-State Electrolyte - Tan, Deming; Wang, Faxing; Pietsch, Tobias; Grasser, Matthias A.; Doert, Thomas; Ruck, Michael (ACS Applied Energy Materials, 2019)
Li-ion conductive polycrystalline Li4B7O12Cl to be used as a solid-state electrolyte was successfully synthesized by an ionothermal route at a low temperature. The reaction of lithium acetate dihydrate, boric acid, and copper(II) chloride dihydrate in trihexyltetradecylphosphonium chloride at 130 °C led to single-phase Li4B7O12Cl within 10 h. Li4B7O12Br was also successfully synthesized in a similar way. The ionic conductivity, activation energy, and electrochemical window of Li4B7O12Cl electrolyte were measured. A relatively high ionic conductivity of 3 × 10-4 S cm-1 at room temperature was detected. A linear sweep voltammogram of the Li4B7O12Cl electrolyte exhibited an electrochemical stability of up to 4.3 V vs. Li/Li+ under the measured conditions. The fabricated Li ∥ Li4B7O12Cl ∥ Li symmetrical cell exhibits a relatively low voltage hysteresis of 120 mV for 60 cycles.
CRIS-Team Scopus Importer:2022-04-14
Keywords: ionic liquids; ionothermal; Li; low-temperature synthesis; solid electrolytes; solid-state lithium batteries